The flamework for fiscal policy in EMU : what future after five years of experience - Flores, Elena; Giudice, Gabriele; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2005)
This paper reviews the first five years of experience with the working of the EMU framework for fiscal policy in EMU. It is argued that the balance with the fiscal framework of EMU so far is mixed. The EMU framework has contributed to avoid large fiscal imbalances in EU Member States and has evolved continuously to deal with a number of budgetary challenges connected to the conduct of fiscal policy and the assessment of budgetary developments in the short, medium and long run. However, problems with the implementations of the rules have emerged, and the ownership of the framework should be re-established. We argue in favour of further improvements within the framework of the Treaty along the following directions: • increased focus on debt and sustainability; • better account of country-specific factors in the definition of medium-term targets; • better enforcement of the rules; • improved implementation of the excessive deficit procedure; • greater account of the Lisbon goals in applying the EMU framework for economic policy co-ordination and budgetary surveillance.
Economic Papers